Value Based and Intelligent Asset Management 2019
DOI: 10.1007/978-3-030-20704-5_13
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Roles of Digital Twin in CPS-Based Production Systems

Abstract: The Digital Twin (DT) is one of the main concepts associated to the Industry 4.0 wave. This term is more and more used in industry and research initiatives; however, the scientific literature does not provide a unique definition of this concept. The paper aims at analyzing the definitions of the DT concept in scientific literature, retracing it from the initial conceptualization in the aerospace field, to the most recent interpretations in the manufacturing domain and more specifically in Industry 4.0 and smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Scholars' research on the theory of digital twin has been carried out rapidly. Zhuang [3] summarized the basic connotation of product digital twin in smart manufacturing, proposed the architecture of product digital twin, and elaborated the implementation paths of product digital twin in the product design phase, manufacturing phase, and service phase; Negri [4] elaborated the digital twin in the field of aerospace, Industry 4.0, and smart manufacturing Definition, and summarized the role assumed by digital twin technology in CPS-based industrial systems, which provides an important reference for researchers in the field of smart manufacturing; Tao [5] pointed out the core issues that need to be solved in digital twin technology at the levels of data management, model construction, and expert cooperation, and put forward suggestions for unifying data and modeling standards, sharing data and models, and innovating service improvement. In recent years, digital twins have been spreading more and more widely, and digital twins have also been applied to electric power [6] , agriculture [7] , ships [8] , vehicles [9] and other industries.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars' research on the theory of digital twin has been carried out rapidly. Zhuang [3] summarized the basic connotation of product digital twin in smart manufacturing, proposed the architecture of product digital twin, and elaborated the implementation paths of product digital twin in the product design phase, manufacturing phase, and service phase; Negri [4] elaborated the digital twin in the field of aerospace, Industry 4.0, and smart manufacturing Definition, and summarized the role assumed by digital twin technology in CPS-based industrial systems, which provides an important reference for researchers in the field of smart manufacturing; Tao [5] pointed out the core issues that need to be solved in digital twin technology at the levels of data management, model construction, and expert cooperation, and put forward suggestions for unifying data and modeling standards, sharing data and models, and innovating service improvement. In recent years, digital twins have been spreading more and more widely, and digital twins have also been applied to electric power [6] , agriculture [7] , ships [8] , vehicles [9] and other industries.…”
Section: Introductionmentioning
confidence: 99%
“…This involves the use of engineering processes to define the products or modules/systems, as well as the production systems needed to create them [2]. Wireless sensor networks, edge computing, cloud computing, the fifth-generation cellular network (5G), IoT, Big data, and other technologies are continually growing and have enormous potential in every industry field [3][4][5][6][7][8]. All of these technologies enable the integration of the physical and digital worlds, which is an unavoidable trend in order to address the market's increasing complexities and high demands.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at the data sources in the twin system, in 2017, Uhlemann [3][4] proposed a data acquisition method based on multimodality to establish a digital twin system for the product life process, which shortened the data acquisition time and the creation delay of the digital twin system, thereby improving the consistency of virtual products and digital products. In 2018, Tao Fei et al [5][6] analyzed the research of digital twin technology in the field of model definition, proposed a five tier structure model of digital twin technology and six application criteria of digital twin drive, Zhuang Cunbo et al [7][8] designed the architecture of product digital twin, and demonstrated in detail the implementation methods of product digital twin in the design, manufacturing, service and maintenance stages.…”
Section: Introductionmentioning
confidence: 99%